Dampak Akuisisi Terhadap Return Saham Perusahaan Pengakuisisi - Ainin Afiati Murtiningsih; Indro Herry Mulyanto (Jurnal Paradigma, 2018)
The announcement of acquisition made by a company may affect the stock price of the acquired company.